Current Trends in Ensuring the Sustainable Development of Aviation - Cherniak, Larysa; Madzhd, Svitlana (My University, 2021)
The modern aviation industry is developing rapidly, thus creating many benefits and opening new opportunities for society. But, at the same time, the development of this industry creates stress for all the environment components, to a greater or lesser extent. Importantly, thedevelopment of aviation industry negatively affects people and other living organisms not onlylocally but also globally. Therefore, the issues of ensuring the sustainable development of the modern aviation industry are extremely relevant and require complex and targeted actions

Сучасна авіаційна промисловість стрімко розвивається, створюючи чимало переваг і відкриваючи нові можливості для суспільства. Але, в той же час, розвиток цієї галузі більшою чи меншою мірою створює стрес для всіх компонентів навколишнього середовища. Важливо, що розвиток авіаційної промисловості негативно впливає на людей та інші живі організми не лише локально, а й глобально. Тому питання забезпечення сталого розвитку сучасної авіаційної галузі є надзвичайно актуальними та потребують комплексних і цілеспрямованих дій
Keywords: environment; навколишнє середовище; aircraft construction; aircraft construction; кафедра екології та екоменеджменту